問題文全文(内容文):
次式を証明せよ。
$\displaystyle \sum_{i=1}^n k^2=\frac{1}{6}n(n+1)(2n+1)$
$\displaystyle \sum_{i=1}^n k^3=\{ \frac{1}{2}n(n+1)\}^2$
次式を証明せよ。
$\displaystyle \sum_{i=1}^n k^2=\frac{1}{6}n(n+1)(2n+1)$
$\displaystyle \sum_{i=1}^n k^3=\{ \frac{1}{2}n(n+1)\}^2$
単元:
#数列#数列とその和(等差・等比・階差・Σ)#数学(高校生)#数B
指導講師:
【楽しい授業動画】あきとんとん
問題文全文(内容文):
次式を証明せよ。
$\displaystyle \sum_{i=1}^n k^2=\frac{1}{6}n(n+1)(2n+1)$
$\displaystyle \sum_{i=1}^n k^3=\{ \frac{1}{2}n(n+1)\}^2$
次式を証明せよ。
$\displaystyle \sum_{i=1}^n k^2=\frac{1}{6}n(n+1)(2n+1)$
$\displaystyle \sum_{i=1}^n k^3=\{ \frac{1}{2}n(n+1)\}^2$
投稿日:2022.02.21